Characteristics of nitrogen removal and nitrous oxide production in CANON process. Issue 4 (22nd July 2013) - Xiao, Pengying; Cai, Qing; Zhang, Daijun; Yao, Zongbao; Lu, Peili
Abstract BACKGROUND Ammonia (NH3) was converted to dinitrogen gas (N2) cooperating between ammonia‐oxidizing bacteria (AOB) and anaerobic ammonia‐oxidizing bacteria (AnAOB) with low amounts of nitrous oxide (N2O) as the side‐product in the completely autotrophic nitrogen removal over nitrite (CANON) process. Contributions of anaerobic ammonia oxidation (anammox) by AnAOB and nitrifer denitrification by AOB for nitrogen (N) removal and the characteristics of N2O production were investigated comprehensively in this study. RESULTS AnAOB was the dominant contributor to autotrophic nitrogen removal, and the contributions from nitrifier denitrification were less than 13.55% of the N removal. Nitrite (NO2‐) addition increased the N removal rate of the CANON process under oxygen limiting conditions; N2O primarily produced from nitrifier denitrification by AOB was 0.41–7.25% of the N removal, and there was a positive correlation between NO2‐ concentration and N2O production. Under anaerobic conditions, 10 mmol L−1 methanol did not completely inhibit the activity of AnAOB, but N2O production rate was significantly decreased with the addition of methanol. CONCLUSION The contribution from nitrifier denitrification by AOB was less than 13.55% of the N removal, and AnAOB played an impotent role in N2O production by providing hydroxylamine as an electron donor for AOB to reduce NO2‐ in the CANON process. © 2013 Society of Chemical Industry